Digital Dilemma: Challenges and Solutions in the Use of AI for Academic Writing among English Language Education Students - Yuliana Mangendre; Desriani Nggolaon; Nurlaela Nurlaela (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2026)
This study examines the challenges and ethical dilemmas faced by English Language Education students at Muhammadiyah University of Luwuk in using Artificial Intelligence (AI) for academic writing. It identifies patterns of AI usage in the writing process. Data were collected through questionnaires and interviews. The findings show that although AI improves writing quality, increases time efficiency, and helps generate ideas, its use raises concerns. The main challenges include overreliance on AI, reduced critical thinking, potential plagiarism, difficulty creating effective prompts, overly general or irrelevant outputs, and unverifiable references. Interview results reveal linguistic and stylistic features of AI-generated texts. Students acknowledge the risks of misuse and propose solutions, including ethics training, university guidelines, mentoring, and access to reliable tools. This study recommends developing clear institutional policies, improving AI literacy, and implementing strict oversight to ensure AI is used ethically and effectively as a support tool rather than a substitute for students’ abilities.